PECULIARITIES OF EPITHETS FUNCTIONING IN THE SHORT STORIES BY H. P. LOVECRAFT - Torhovets, Y.; Andronova, M. (Studia Philologica, 2019)
The article presents the analysis of the role of epithets in the creation of mysterious atmosphere and awaking the reader’s feeling of fear and disgust in short stories written by H. P. Lovecraft. The peculiar feature of “cosmic horror” in the short stories under analysis is the use of epithets in order to appeal to sensory feelings, which are the powerful tool for the creation of disgusting and terrible images and feelings. By means of interdisciplinary approach, the epithets have been grouped according to the location of sensory receptors into visual, auditory and olfactory. It has been found that visual epithets constitute the dominant group.